Boosting the Electrochemical Performance of V2O3 by Anchoring on Carbon Nanotube Microspheres with Macrovoids for Ultrafast and Long‐Life Aqueous Zinc‐Ion Batteries. Issue 9 (16th August 2021) - Park, Jin‐Sung; Yang, Sungjin; Kang, Yun Chan
Abstract: Zinc‐ion batteries (ZIBs) are next‐generation energy storage systems with high safety and environmental friendliness because they can be operated in aqueous systems. However, the search for electrode materials with ideal nanostructures and compositions for aqueous ZIBs is in progress. Herein, the synthesis of porous microspheres, consisting of V2 O3 anchored on entangled carbon nanotubes (p‐V2 O3 ‐CNT) and their application as cathode for ZIBs is reported. From various analyses, it is revealed that V2 O3 phase disappears after the initial charge process, and Zn3+ x (OH)2+3 x V2− x O7−3 x ∙2H2 O and zinc vanadate (Zn y VOz ) phases undergo zinc‐ion intercalation/deintercalation processes from the second cycle. Additionally, the electrochemical performances of p‐V2 O3 ‐CNT, V2 O3 ‐CNT (without macrovoids), and porous V2 O3 (without CNTs) microspheres are compared to determine the effects of nanostructures and conductive carbonaceous matrix on the zinc‐ion storage performance. p‐V2 O3 ‐CNT exhibits a high reversible capacity of 237 mA h g −1 after 5000 cycles at 10 A g −1 . Furthermore, a reversible capacity of 211 mA h g −1 is obtained at an extremely high current density of 50 A g −1 . The macrovoids in V2 O3 nanostructure effectively alleviate the volume changes during cycling, and the entangled CNTs with high electrical conductivity assist in achieving fast electrochemical kinetics. Abstract : Herein, V2 O3 microspheres with internal macrovoids, composited with entangled carbon nanotubes are prepared and applied as cathode for aqueous zinc‐ion batteries, where the electrochemical conversion reaction mechanism is investigated by in/ex situ analyses. The cathode exhibits stable cycle life up to 5000 cycles at 10 A g −1, and ultrafast rate capability (211 mA h g −1 at 50 A g −1 ).